Adapting and testing of DeprEnd EMDR therapy for major depressive disorder: a study protocol of mixed method randomized controlled trial - Anwar, Khan; Amalia, Madihie; Maqsood, Haider; Sajjad, Haidee; Rawaiz, Khan; Ali, Bahadar (Springer Nature Limited, 2026)
Background: Major Depressive Disorder (MDD) is a significant contributor to the global burden of disease, with a high prevalence in Pakistan. MDD is treatable, and Eye Movement Desensitization and Reprocessing (EMDR) therapy is recognized as an effective treatment worldwide. However, EMDR therapy, rooted in Western psychological frameworks, may require cultural and methodological adaptation to fit clients' needs in Pakistan. Notably, there is a lack of research on adapting EMDR therapy in Pakistan, and scarce studies on its effectiveness through online modalities. To bridge these research gaps, this study has two aims: first to develop an adapted DeprEnd EMDR therapy protocol in Pakistan, second, to test its feasibility, relevance, and clinical effectiveness across in-person and online modalities. Methods: This research adopts a mixed-mode exploratory sequential randomized controlled trial design. In the first phase, an exploratory qualitative approach will be utilized to culturally and methodologically adapt DeprEnd EMDR therapy protocol through narrative review and focus group discussion. Data will be qualitatively analyzed. This phase has been previously reported in a separate peer-reviewed publication. In the second phase, a randomized controlled trial design will be used to test feasibility, relevance, and clinical effectiveness of adapted DeprEnd EMDR therapy protocol. Initially, it will be pilot tested among 25 handful clients, and later an estimated sample of 80 clients will be selected to test it on a large scale. Clients will be randomized via covariate-adaptive technique to in-person and online arms with a 1:1 ratio. Symptom-related data will be collected at the baseline, midpoint, post-treatment, and followup stages. Data will be analyzed using a combination of univariate and multivariate statistics.